IMPLIKASI STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN DENGAN KEPUTUSAN KEUANGAN SEBAGAI VARIABEL INTERVENING (SEKTOR MANUFAKTUR BEI) - Reza Febrian; Arief Tumanggor; Muslim Marpaung (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2022)
The value of the company is one of the shareholders reference before investing in a company and the company's value can not be separated from the influence of financial decision of by the owner of the company. The aim of the research was to find out the implication of ownership structure on companies’ value with financial decision as intervening variable in manufacturing companies listed in Indonesia Stock Exchange. The samples consist of 34 manufacturing companies listed in Indonesia Stock Exchange during the period of 2010-2014. The research method used structural equation model (SEM) with the help of software AMOS 16,0. The Result of the research indicate that ownership structure affects funding decision, deviden policy, and companies’ value, but it does not affect investment decision. Investment decision, funding decision, and deviden policy affect companies’ value. Furthermore, investment decision, funding decision and deviden policy can function as intervening variable in the effect of ownership structure on companies’ value.